Ramp morphology controlling the facies differentiation of a Late Ordovician reef complex at Bachu, Tarim Block, NW China - Zhang, Yuandong; Munnecke, Axel; Wang, Jianpo; Lin, Yue (Lethaia, 2015)
A carbonate ramp in the shallow-marine northwestern part of the Central Tarim Uplift, Bachu, NW China, exhibits an extraordinary Late Ordovician reef complex along the Lianglitag Mountains, exposed for a distance of about 25 km. Seven localities within the 'Middle Red Limestone' of the Upper Member of the Lianglitag Formation (Katian, Late Ordovician) illustrated the changes in biofacies and lithofacies: northern, seaward-directed patch reefs are replaced towards the south by coeval grain banks. The patch reef units are dominated by microbial and calcareous algal components. The reefs at the northernmost locality are knoll-shaped, kalyptra-shaped or irregularly shaped with sizes of individual reefs increasing from about 2 m in height and diameter. Stratigraphically upward, reefs notably expand to larger structures by several mounds coalescing; they are generally about 10 m thick and tens of metres in lateral extent. The maximum thickness of the main patch reef is more than 30 m, and its diameter is around 100 m. The reefal units turn into biostromes with gentler relief southward and still further south grade into banks composed of peloids and coated grains. The southernmost locality is still a shallow-water bank, and the coastline is not documented in the study area. The present evidence indicates that the Late Ordovician palaeo-oceanography provided a number of environments for the optimal growth of carbonate build-ups; microbial-calcareous algal communities could thrive in areas where the innovative metazoan reef frameworks consisting of corals and stromatoporoids did not play a significant role. The ramp morphology, especially changes in water depth, controlled the configuration of the reef complex.
Keywords: Bachu; Late Ordovician; Lianglitag Formation; NW China; Reef complex; Tarim Block